2021
DOI: 10.3390/app11062764
|View full text |Cite
|
Sign up to set email alerts
|

Potential Instability and Malfunction of Knee Joints with Vastus Medialis Impairment after Total Knee Arthroplasty

Abstract: Four pairs of fresh-frozen cadaver knees (eight knees, four male knees) with a mean age of 72 ± 7 years were used for tests involving a customized simulator capable of controlling quadriceps loading conditions. The muscle force distribution of the quadriceps for the normal loading condition was applied on the basis of muscle cross-sectional area data, as previously reported (VM: 31 N; RF/VI: 49 N; VL: 45 N). To simulate vastus medialis (VM) impairment, we set the muscle force for VM in the muscle force distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Second, we only evaluated the VM status among the quadriceps muscles. However, numerous studies have found that VM performs the main function during ambulation among quadriceps muscle groups and that VM impairment increases joint reaction force and leads to potential complication after TKA [7,34,35]. We believe that the VM alone could reflect the state of the entire quadriceps muscle.…”
Section: Discussionmentioning
confidence: 87%
“…Second, we only evaluated the VM status among the quadriceps muscles. However, numerous studies have found that VM performs the main function during ambulation among quadriceps muscle groups and that VM impairment increases joint reaction force and leads to potential complication after TKA [7,34,35]. We believe that the VM alone could reflect the state of the entire quadriceps muscle.…”
Section: Discussionmentioning
confidence: 87%